Macroinvertebrate traits in Arctic streams reveal latitudinal patterns in physiology and habits that are strongly linked to climate - Lento, Jennifer; Lau, Danny C. P.; Brittain, John E.; Culp, Joseph M.; Goedkoop, Willem (Frontiers in Ecology and Evolution, 2023)
Arctic freshwater ecosystems are undergoing rapid environmental transformation because of climate change, which is predicted to produce fundamental alterations in river community structure and function. We explored how climate change affects benthic invertebrate communities of Arctic streams by examining patterns of their biological traits along latitudinal and climatic gradients in eastern North America (Canada) and northwestern Europe (Sweden, Norway). Despite differences in taxonomic composition between continents, we identified similarities in the functional trait niche (FTN) of predominant macroinvertebrate taxonomic groups. Trait composition differed by latitude in eastern Canada, with a predominance of cold-tolerant taxa, tubular body shape, and cased and attached habits at the highest latitudes. Differences in trait composition were evident among ecoregions in Europe, with trait dominance at the highest latitudes that was comparable to North America. There was a similar increase in the relative abundance of cold tolerance and tubular body shape and a decrease in obligate shredders and trait richness with decreasing temperatures across both continents. These patterns are indicative of FTNs that include physiological traits and habits that are advantageous for the low temperatures, short ice-free period, and low riparian vegetation cover at the highest latitudes. We predict that climate change will lead to an increase in functional diversity at high latitudes, as organisms with trait modalities that are currently only found at lower latitudes move northward. However, this change in trait composition will be mediated by the effect of spatial connectivity on dispersal ability, with slower change occurring on Arctic islands. These findings can 2 This is a provisional file, not the final typeset article support modelling of future change in Arctic freshwater assemblages in response to ongoing climate change.